2015
DOI: 10.1111/1751-7915.12329
|View full text |Cite
|
Sign up to set email alerts
|

Ustilago maydis produces itaconic acid via the unusual intermediate trans‐aconitate

Abstract: SummaryItaconic acid is an important biomass‐derived chemical building block but has also recently been identified as a metabolite produced in mammals, which has antimicrobial activity. The biosynthetic pathway of itaconic acid has been elucidated in the ascomycetous fungus A spergillus terreus and in human macrophages. In both organisms itaconic acid is generated by decarboxylation of the tricarboxylic acid (TCA) cycle intermediate cis‐aconitate. Here, we show that the basidiomycetous fungus U stilago maydis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
143
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 65 publications
3
143
0
Order By: Relevance
“…However, further development by the above-described strategies could still eventually yield a competitive system. In addition, the biosynthesis pathways for itaconic acid as well as for the potentially interesting glycolipids have been described in detail, and initial attempts of metabolic engineering have already demonstrated their potential to increase productivity (27,86,87).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further development by the above-described strategies could still eventually yield a competitive system. In addition, the biosynthesis pathways for itaconic acid as well as for the potentially interesting glycolipids have been described in detail, and initial attempts of metabolic engineering have already demonstrated their potential to increase productivity (27,86,87).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Ustilaginaceae smut fungi are promising natural producers of organic acids (21,26,27). Within this group of biotrophic plant pathogens, Ustilago maydis is of increasing interest, not least due to its long history of intensive investigation as a paradigm of plant-pathogen interaction (28).…”
mentioning
confidence: 99%
“…Huang et al [33] overexpressed cadA and mfsA (major facilitator superfamily transporter) genes in A. terreus and obtained enhanced IA production level by 9.4 and 5.1% in shake flasks, respectively, in comparison to wild type. Geiser et al [23] reported that overexpression of a pathway-specific transcription factor (Ria1) or a mitochondrial tricarboxylic acid transporter (Mtt1) in U. maydis resulted in a 2-fold increase in IA yield.…”
Section: Recombinant Microorganisms For Production Of Itaconic Acidmentioning
confidence: 99%
“…Recently, Gieser et al [23] showed that the fungus Ustilago maydis, a phytopathogenic basidiomycete, uses an alternative pathway and produces IA via trans-aconitate, the thermodynamically favored isomer of cis-aconitate (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation